Capacité de réception touristique et pauvreté - Bruno Marques (Études Caribéennes)
Based on a stylized model of a two-sector economy frequented by tourists, this paper argues that the tourism-poverty link may be understood in a reverse causality; from poverty to tourism. This "reverse" understanding is based on two elements: Tourism necessarily presents a choice for residents: what part(s) of the local product should tourists be allowed access to? When the flow of tourism is constrained, the willingness of local residents to accommodate tourists is more heavily influenced by quality of life.